Rapid Diagnosis of Babesia gibsoni by Point‐of‐Need Testing by Insulated Isothermal PCR in Dogs at High Risk of Infection. (28th January 2018) - Cooke, K.L.; Frenzer, P.; Tucker, S.J.; Crawford, P.C.; Kirk, S.K.; Levy, J.K.
Abstract : Background: Dogs seized by law enforcement agencies during dogfighting investigations are at increased risk of Babesia gibsoni infection. A rapid and cost‐effective diagnostic test would increase the feasibility of mass screening of dogs for infection and monitoring treatment efficacy in B. gibsoni ‐infected dogs. Objective: To determine the performance of a point‐of‐need insulated isothermal PCR (iiPCR) test for diagnosis of B. gibsoni in dogs rescued in dogfighting investigations. Animals: Two hundred and thirty‐three dogs seized in dogfighting investigations. Methods: Cross‐sectional study. Whole blood samples were tested for B. gibsoni and Babesia spp. by iiPCR. Results were compared to a reference standard comprised of concordant results from real‐time PCR in a commercial diagnostic laboratory and antibody titers. Results: The iiPCR system was quick to learn, portable, and had a short processing time of <2 hours. Sensitivity and specificity of the iiPCR assay for B. gibsoni were 90% (95% confidence interval [CI] 81–95%) and 99% (CI, 95–100%), respectively. Sensitivity and specificity of the iiPCR assay for Babesia spp. were 87% (CI, 78–93%) and 98% (CI, 0.94–99%), respectively. Conclusions and Clinical Importance: The iiPCR system produced few false‐positive results, indicating that positive results are likely to represent true infections when used in high‐risk animals. The iiPCR system can fail to identify 10–15% of truly infected dogs. However, the portability, speed, and economy of the iiPCR system compared to testing through a reference laboratory can allow rescue groups to screen and identify infection in more dogs.